Emission of polluting gases in civil construction: generating theme for curriculum integration (Research, Society and Development, 2021)
In technical education integrated to high school, one of the greatest challenges for teachers is to bring the labor market closer to the contents studied in the classroom. Issues related to the environment and sustainability are examples of generative themes, which can and should be discussed in an interdisciplinary way, in the integrated secondary education curricula. Therefore, the objective of this article was to propose a case study with a different methodology, having as its base theme the release of polluting gases in civil construction. The work was developed with students from the 2nd grade of integrated technical education in Buildings, from a public school in the State of Paraíba, and the method was divided into three stages: lecture in Chemistry II, visits and analysis of works, and presentation of the results for the class. The works presented by the students evidenced the construction of important understandings and interactions between contents and concepts in the basic and technical areas.